Haemodynamically dependent valvulogenesis of zebrafish heart is mediated by flow-dependent expression of miR-21 - Banjo, Toshihiro; Grajcarek, Janin; Yoshino, Daisuke; Osada, Hideto; Miyasaka, Kota Y.; Kida, Yasuyuki S.; Ueki, Yosuke; Nagayama, Kazuaki; Kawakami, Koichi; Matsumoto, Takeo; Sato, Masaaki; Ogura, Toshihiko (Nature Communications, 2013)
Heartbeat is required for normal development of the heart, and perturbation of intracardiac flow leads to morphological defects resembling congenital heart diseases. These observations implicate intracardiac haemodynamics in cardiogenesis, but the signalling cascades connecting physical forces, gene expression and morphogenesis are largely unknown. Here we use a zebrafish model to show that the microRNA, miR-21, is crucial for regulation of heart valve formation. Expression of miR-21 is rapidly switched on and off by blood flow. Vasoconstriction and increasing shear stress induce ectopic expression of miR-21 in the head vasculature and heart. Flow-dependent expression of mir-21 governs valvulogenesis by regulating the expression of the same targets as mouse/human miR-21 (sprouty, pdcd4, ptenb) and induces cell proliferation in the valve-forming endocardium at constrictions in the heart tube where shear stress is highest. We conclude that miR-21 is a central component of a flow-controlled mechanotransduction system in a physicogenetic regulatory loop.
Gesehen am 03.11.2020